Feasibility Study on Establishment of Spa’tisfaction Innovation of Oil with Charcoal in Lagro, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Spas are at the forefront of a holistic health and wellness movement that is taking over the world as individuals learn that the most effective approach to health is maintaining a balanced body and lifestyle. The researchers decided to create a body spa and massage business because some of the customers need to relax. The researchers conceptualized the idea of innovating a spa to be appreciatedby everyone from young people to old ones. Hence, the researchers created Spa’Tisfasction, which is a spa house that innovates oil with charcoal and other oils. Spa’Tisfasction is located at 1B Quirino Highway Corner AscensionAve.,Greater Lagro, Novaliches, Quezon City. The researchers pursued this concept to show the possible customers regarding the effectiveness of the health benefits of charcoal oil used in the spa. Spa’Tisfasction consists of 5 people, and the owners invested P200,000each to create a new and delightful spa to gain personal and professional growth. The estimated purpose starting capital of the researchers must beat least P500,000. The study came up with the idea that business will grow and will become successful with the help of the result taken from respondents. The researchers created a questionnaire that includes the demographic profile of the respondents and different sets of questions, with corresponding indicators in terms of the market segment. The researchers gathered the data and analyzed the results. Information gathered from the respondents was interpreted and utilized in gaining new ideas and innovation of the product, price, place, and promotion. The researchers gathered some information by using survey questionnaires throughaquantitative technique to know the reaction of the respondents to the product of Spa’tisfaction based on the survey that involved50 respondents. A total of44% of the respondents areaged36–55 years old, 24% of the respondents areaged26–35years old. A total of 56% of the respondents were male, and 44% of the respondents were male, most of which are married. 58% are employees while 30% are unemployed. A total of 44%of the respondents preferred charcoal oil to be used for massage. A total of 90%of the respondents wanted a whole-body massage,6%of the respondents wanted a facial, and 4% of the respondents wanted water/heat treatment. The respondents’ budget for massage services ranged from P500 to P1,000. A total of 26%of the respondents preferred finding the business on Facebook. Based on the study and findings conducted, the researchers concluded that the Spa’Tisfaction is feasible and viable to the market. The researchers proved that using charcoal oil in the spa has a higher possibility of being patronized by the customers. The technical viability was applied to both skills and knowledge,especially to improvethe services. The researchers also came up with financial projections consisting of an income statement, projected financial position, cash flow return on investment, and a statement of changes in equity. According to the researchers’ study, the products and services are secured, and the monitoring process will be effective to avoid financial loss. The reasonable markup on the product will help the business maintain loyal customers.
Keywords: accrual, charcoal, feasibility, furniture and fixture, holistic health, hydro therapy, spa, thalasso therapy, wellness